Correlation between Spiritual Leadership and Occupational Conflict - Namdar, Masoumeh; Zagheri Tafreshi, Mansoureh; Atashzadeh-Shoorideh, Foroozan; Nasiri, Maliheh (Advances in Nursing & Midwifery, 2019)
Abstract Introduction: Nurses as the largest group among the healthcare staff sustain continual environmental pressures and changes. Hence, the incidence of conflict among nurses is something normal due to extensive interactions with various people. Managers can make the organizational activity more effective and efficient by the use of innovative leadership styles based on internal motivation and appropriate management of conflict. This study determined the correlation between spiritual leadership and occupational conflict of nurses employed at selected academic hospitals affiliated to Shahid Beheshti University of Medical Sciences in 2017. Methods: 287 nurses employed at various wards of academic hospitals of Shahid Beheshti University of Medical Sciences, Tehran, Iran, were enrolled in this descriptive-correlational study using convenient sampling method. The data were collected using two questionnaires; “Spiritual Leadership” and “Occupational Conflict” and analyzed with SPSS.18. Results: 261 nurses completed questionnaires and resend them. The findings showed that the maximum score obtained by nurses about their head nurse’s spiritual leadership style belonged to “altruistic love” (14.46 out of 25). In addition, the highest score about their occupational conflict belonged to “interclass conflict” (10.98 out of 16). Generally, there was a significant correlation between spiritual leadership and occupational conflict (P<0.001, r=0.522). Conclusions: The findings on the correlation between the nurses’ perspectives about spiritual leadership and occupational conflict indicated that the application of innovative styles such as spiritual leadership to reduce nurses’ occupational conflict in the Iranian healthcare system demands more investigations. It can serve as the managers’ guide in choosing the most effective leadership style to diminish occupational conflict among nurses and reach the highest levels of outcomes in the organization.